Urban Nature and Biodiversity for Cities : Policy Brief - Guerry, Anne D. (World Bank, Washington, DC, 2021)
This is the urban century; over half of humanity now lives in cities and more than 70 percent are expected to do so by 2050. Today, cities are hubs of social interchange, economic vitality, and innovation. Yet the pace and scale of global transformation in where and how people live pose threats to biodiversity and nature that demand serious attention. In today’s complex world, it is natural - and sometimes necessary - to compartmentalize sectors and realms of experience. Thus, urban planning traditionally occurs without much consideration of biodiversity and nature. It is therefore imperative that cities are designed in ways that maintain the provision of ecosystem services and that national and international conservation plans consider urban centers. This report presents the scientific basis for why and how incorporating biodiversity and nature into urban design is crucial for achieving sustainability, livability, resilience, and equity in cities and beyond. Section one defines key terms and concepts, section two examines what is at stake regarding urban nature and biodiversity, section three explores what urban leaders can do to promote them, section four offers some practical tools and approaches for incorporating urban nature and biodiversity into urban decision-making, and section five concludes.